TEACHING ENGLISH PREPOSITION USING TOTAL PHYSICAL RESPONSE IN THE FIFTH GRADE STUDENTS OF SD N 01 KENDALSARI PETARUKAN PEMALANG IN 2009/2010 ACADEMIC YEARS - KURIYANTI , HESTRI (2010)
This research paper is aimed at describing the implementation of Total Physical Response (TPR) method in the fifth grade students of SD N 01 Kedalsari Petarukan, Pemalang and the problem faced by the teacher and the students in teaching learning process using TPR. This study is a descriptive qualitative research. The data used in this research are derived from event, document, and informant. The data are gained from observation and interview with the teacher and the students. Based on the observation and interview, the writer draws several conclusions on the implementation of TPR in teaching English at SD N 01 Kendalsari Petarukan Pemalang. First, TPR is implemented in teaching English at SD N 01 Kendalsari Petarukan Pemalang. The teacher gives command and gets the students performs and action. Teacher uses teaching aids and focuses on body movement. So, the teacher can bring and locate the students in the positive teaching situation, relax and measure student's ability. Second, in teaching English using TPR, the teacher has problem, that is the time allotment is too short, different capability of students, and the students are not diligent at home, the students unwillingness to listen, the learners mood, the teacher needs more energy to teach the students, needs a lot of media and spent a lot of time in teaching activities. The learners' problems are they doubt with the method, so they refuse to move when commanded by the teacher and the students still confuse about the preposition word.